2018
DOI: 10.1155/2018/7805857
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Use of Prealbumin as a Tool for Nutritional Assessment in Adults Coinfected with HIV and Intestinal Helminth Parasites in KwaZulu-Natal, South Africa

Abstract: Serum prealbumin is considered to be as important as albumin in the nutritional status assessment. However, there is relatively little evidence of its advantage over the commonly used albumin. This study investigated the use of prealbumin compared to albumin as a marker of nutritional status in adults singly and dually infected with human immunodeficiency virus (HIV) and intestinal helminths, with or without inflammatory conditions, in different body mass index (BMI) categories. This cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Among the anthropometric parameters, BMI showed significant positive correlation with serum prealbumin levels. This is consistent to prior studies, where BMI was shown to have positive correlation with prealbumin level [28][29]. Height and weight showed positive correlation, waist circumference, hip circumference and waist to hip ratio showed negative correlation with serum prealbumin level.…”
Section: Discussionsupporting
confidence: 92%
“…Among the anthropometric parameters, BMI showed significant positive correlation with serum prealbumin levels. This is consistent to prior studies, where BMI was shown to have positive correlation with prealbumin level [28][29]. Height and weight showed positive correlation, waist circumference, hip circumference and waist to hip ratio showed negative correlation with serum prealbumin level.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous studies have found that a series of parameters on admission are correlated with mortality risk (34), there is limited information in the existing literature regarding the relationship between nutrition indexes and disease progression in SARS-CoV-2-infected patients. Several studies have reported the value of nutritional indicators represented by PAB on determining the severity of viral infections and predicting the prognosis of patients (35,36). In addition, there is some literature describing the roles of inflammatory indicators (hsCRP and PCT), coagulation indicators (DD), and the number of lymphocytes in monitoring the disease progression during viral infection and prediction of disease outcome (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…23 The association between HIV and helminth co-infections and lower biochemical micronutrients, protein and carbohydrate levels in humans has also been shown. 24 Additionally, several nutrient deficiencies have been found to increase the likelihood of HIV and helminth co-infection. 24 It is understood that various nutrient deficiencies cause impaired immunity.…”
Section: Helminth and Hiv/aids Co-infection Immune Responsesmentioning
confidence: 99%
“…24 Additionally, several nutrient deficiencies have been found to increase the likelihood of HIV and helminth co-infection. 24 It is understood that various nutrient deficiencies cause impaired immunity. 23 These findings illustrate the need for further research that may better describe and explain the effects of helminth immune modulation in individuals co-infected with HIV, leading to successful development of helminth and HIV-related vaccines which will be effective and timely accessible to save lives and improve the general health of those co-infected.…”
Section: Helminth and Hiv/aids Co-infection Immune Responsesmentioning
confidence: 99%